2015
DOI: 10.3109/17518423.2015.1022809
|View full text |Cite
|
Sign up to set email alerts
|

Interarticulator coordination in children with and without cerebral palsy

Abstract: The current study investigates how interarticulator coordination changes across speaking tasks varying in articulatory and linguistic demands for children with CP and their typically-developing peers. Articulatory movements from 12 children with spastic CP (7M, 5F, 4–15 years of age) and 12 typically-developing age- and sex-matched peers were cross-correlated to determine the degree of spatial and temporal coupling between the upper lip and jaw, lower lip and jaw, and upper and lower lips. Spatial and temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 47 publications
2
33
0
2
Order By: Relevance
“…These findings also appear to parallel reports of reduced oromotor performance during speech production including descriptions of increased lip and jaw displacements [14] and reduced coordination [15]. These articulatory differences may account for the speech deficits commonly observed in this group, including a slower speaking rate [14] and reduced intelligibility [15].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings also appear to parallel reports of reduced oromotor performance during speech production including descriptions of increased lip and jaw displacements [14] and reduced coordination [15]. These articulatory differences may account for the speech deficits commonly observed in this group, including a slower speaking rate [14] and reduced intelligibility [15].…”
Section: Discussionsupporting
confidence: 80%
“…Fifteen reflective markers were placed on each participant’s face as shown in Fig. 1 [12, 14, 15]. Three spherical reflective markers, approximately 2 mm in diameter, were placed on the jaw using double-sided adhesive hypoallergenic tape.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such formant instability within vocalic segments containing corner vowels could affect vowel space area measurements for children with SMI, as the vowel midpoints may not reflect the ultimate endpoint of the formant trajectory for that phoneme. This hypothesis is also supported by kinematic research, which has demonstrated that children with CP have decreased spatial and temporal coupling between articulators (Nip, 2017) and use larger lip and jaw excursions than TD children in some contexts (Nip, 2013). Alternatively, it is also possible that individual differences among children in the SMI group may have masked group differences in F2 IQR between children with SMI and TD children.…”
Section: F2 Iqrmentioning
confidence: 85%
“…Lee, Hustad, & Weismer, 2014;Weismer, Jeng, Laures, Kent, & Kent, 2001). For children with cerebral palsy (CP), articulatory imprecision is a common perceptual feature of dysarthria (Hustad, Gorton, & Lee, 2010;Nip, 2013Nip, , 2017Workinger & Kent, 1991). Prior research has identified acoustic correlates of reduced intelligibility in children with CP (Higgins & Hodge, 2002;Hsu, Chen, & Cheng, 2013;Hustad et al, 2010;J.…”
Section: Range and Precision Of Formant Movement In Pediatric Dysarthriamentioning
confidence: 99%